Laboratory modular instrumented single screw extruder for optimisation of polymer processing - Gaspar-Cunha, A. (2012)
A laboratory fully modular instrumented single screw extruder designed to gather information on the development along its axis of temperature, mixing, chemical conversion and/or morphology development of a given material is presented. Some of its capabilities are utilised to study the effect of operating conditions and of screw geometry, including conventional versus barrier profiles, on the evolution of the plasticating sequence of a low density polyethylene. Melting of an immiscible polymer blend (polyamide 6/polypropylene) is also investigated and a specific melting mechanism is proposed.